2011
DOI: 10.1186/1471-2466-11-52
|View full text |Cite
|
Sign up to set email alerts
|

Verifying a questionnaire diagnosis of asthma in children using health claims data

Abstract: BackgroundChildhood asthma prevalence is widely measured by parental proxy report of physician-diagnosed asthma in questionnaires. Our objective was to validate this measure in a North American population.MethodsThe 2884 study participants were a subsample of 5619 school children aged 5 to 9 years from 231 schools participating in the Toronto Child Health Evaluation Questionnaire study in 2006. We compared agreement between "questionnaire diagnosis" and a previously validated "health claims data diagnosis". Se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
35
2
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 53 publications
(42 citation statements)
references
References 22 publications
4
35
2
1
Order By: Relevance
“…Yang et al recently reported that when compared to an asthma diagnosis based on claims data, parental report of a doctor diagnosis of asthma was not sensitive (59%) but was specific (95.9%). (37) A larger sample size would have improved the precision of the associations in the subgroups. Some of our associations could be spurious findings.…”
Section: Discussionmentioning
confidence: 99%
“…Yang et al recently reported that when compared to an asthma diagnosis based on claims data, parental report of a doctor diagnosis of asthma was not sensitive (59%) but was specific (95.9%). (37) A larger sample size would have improved the precision of the associations in the subgroups. Some of our associations could be spurious findings.…”
Section: Discussionmentioning
confidence: 99%
“…One study reported a sensitivity of 76.9% and a specificity of 97.5% for current doctor-diagnosed asthma, as determined from medical records 17. Two recent studies of the cumulative incidence of childhood asthma determined from GP (UK-based) or health claims data (Canada) compared with parent-reported diagnosis reported high specificities but relatively low sensitivities 22 23. Finally, de Marco et al 8 found that the question ‘Have you ever had asthma?’ agreed most closely with clinical diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…8 Our algorithm yielded higher specificity and lower sensitivity when compared with a case validation for children with asthma that utilised a single diagnosis code from primary-care administrative data in Ontario, Canada (sensitivity of 91.4% and specificity of 82.9%). 7 In a more comparable study, Xi et al .…”
Section: Discussionmentioning
confidence: 87%